A Review Of The Programs And Activities Of The Generic Mineral Technology Center For Respirable Dust - Robert L. Frantz (Society for Mining, Metallurgy & Exploration, 1986)
The U.S. Bureau of Mines (USBM) established on August 15, 1983, a Generic Mineral f Technology Center (GTC) for Respirable Dust within the Mining and Mineral Resources Research Institutes (MRIs) at The Pennsylvania State University (PSU) and West Virginia University (WW) in association with participating MRIs at Massachusetts Institute of Technology (MIT) and the University of Minnesota (UMN). The primary goal of the Center is to reduce the incidence and severity of respirable dust disease through researching and advancing the fundamental under- standing of all aspects of respirable dust associated with mining and milling and the interaction of dust and lungs. Other Center activities include the training of engineers and scientists, graduate students and undergraduate students through their respective institutions, and the technology transfer to the industry. The Center also serves as the reference center for publications in the respirable dust area.